Innovative Technologies for Utilization and Disinfection of Waste to Ensure Sustainable Development of Civilization - Suvorova, Irina; Kravchenko, Oleg; Baranov, Igor; Goman, Vitaliy (European Journal of Sustainable Development, 2018)
Ensuring sustainable development of civilisation is a major task of modern times. Ecological safety and cleanness of waste utilization and disinfection is one of the global innovation challenges. An essentially new method has been developed for hydrocavitation activation of homogeneous and heterogeneous media. The method enables the production and ecologically safe combustion of new kinds of composite fuels based on off-spec hydrocarbons and different kinds of effluents. This enables solving two problems at the same time – the energy and ecological ones. A methodology is offered for mathematical modelling the fluid dynamics of viscous incompressible fluid flow in intricate passages by using the R?functions method. Its application helped develop new kinds of atomisers for effective mixing, homogenisation, pre-combustion activation and atomisation of highly viscous composite fuels. The tests of the developed devices have confirmed their high effectiveness. Keywords: waste utilization and disinfection, hydrocavitation activation, composite fuels.